1993
DOI: 10.1677/joe.0.1380421
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high-protein feed supplements on concentrations of growth hormone (GH), insulin-like growth factor-I (IGF-I) and IGF-binding protein-3 in plasma and on the amounts of GH and messenger RNA for GH in the pituitary glands of adult rams

Abstract: Three groups of mature rams were maintained on diets of hay, hay + 2% lupin or hay + 2% cowpea for 11 weeks. Serial blood samples were taken at 15-min intervals for 12 h for the determination of GH and IGF-I content by radioimmunoassay and for IGF-binding protein-3 (IGFBP-3) levels by Western blotting. The rams were killed after 77 days of supplementary feeding and their pituitary glands analysed for content of GH and GH mRNA. Mean plasma GH and baseline GH levels were significantly (P < 0.01) decreased in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 39 publications
1
15
1
Order By: Relevance
“…46 and G(5)=1.13. These parameters followed the values reported previously [26,27]. The significance of differences between values were analyzed by ANOVA, and that of differences between specific groups was determined by the subsequent use of the Newman-Keuls test.…”
Section: Discussionmentioning
confidence: 97%
“…46 and G(5)=1.13. These parameters followed the values reported previously [26,27]. The significance of differences between values were analyzed by ANOVA, and that of differences between specific groups was determined by the subsequent use of the Newman-Keuls test.…”
Section: Discussionmentioning
confidence: 97%
“…Another study showed that genetically lean ram lambs had a significant higher rate of growth hormone release after receiving synthetic human pancreatic GH-releasing factor analogue than the fat animals [8]. Collectively, these previous studies suggest that GH release is impaired in genetically fat lambs, which might be expected since plasma GH levels are generally correlated with adiposity/body weight in sheep [37,38,39,40]. In the cohort of animals in this study, we did find negative correlations between body weight and GH concentration, fat index and GH pulses, plasma leptin and GH amplitude and GH baseline and ORX and MCH gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…A cannula (Dwellcath, Tuta Labs, Melbourne, Vic., Australia) was inserted into one external jugular vein and connected to a manometer line, and the cannula was kept patent with heparinized (75 U/ml) saline. Serial blood samples (5 ml) were taken every 10 min for 8 h (08.00–16.00 h) into heparinized tubes to measure plasma GH levels, because plasma levels of this hormone are correlated with adiposity/body weight in sheep [37,38,39,40]. …”
Section: Methodsmentioning
confidence: 99%
“…Plasma GH concentrations increase during chronic feed restriction in the sheep (Waghorn et al 1987, Clarke et al 1993, in contrast to the rat, which exhibits partial or total suppression of pulsatile GH se¬ cretion under conditions of undernutrition (Tannenbaum et al 1977, Sisk & Bronson 1986). In humans, circulating GH is increased by acute feed restriction, but chronic, severe undernutrition is associated with suppressed GH secretion (Hartman et al 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Extraction and analysis ofpituitary GH and GH mRNA GH was extracted from half of the anterior pituitary gland in 0 m HC1 as described previously (Clarke et al 1993). …”
Section: Methodsmentioning
confidence: 99%